Australasian Conference on Information Systems 2018 2018
DOI: 10.5130/acis2018.cn
|View full text |Cite
|
Sign up to set email alerts
|

Privacy Concerns and Acceptance of Government Surveillance in Australia

Abstract: Increases in routine data collection and surveillance in recent years have resulted in ongoing tension between citizens' privacy concerns, perceived need for government surveillance and acceptance of policies. We address the lack of Australia focussed research through an online survey of 100 Australian residents. Data was analysed using PLS, revealing that privacy concerns around collection influence acceptance of surveillance but do not influence enactment of privacy protections. Conversely, respondents' conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(37 citation statements)
references
References 20 publications
(30 reference statements)
5
31
0
Order By: Relevance
“…These results have clear implications for potential corporate and government policy decisions. Historically, Australians have disproportionately trusted government agencies (84%) over private companies like Google and Apple (42%;van Souwe et al, 2017), and only accepted surveillance if it was deemed necessary (Kininmonth et al, 2018). Contrasting these established norms, our results imply that Australians are willing to sacrifice privacy to governments and corporations in order to combat the spread of COVID-19.…”
Section: Hypothetical Tracking Scenariosmentioning
confidence: 65%
See 1 more Smart Citation
“…These results have clear implications for potential corporate and government policy decisions. Historically, Australians have disproportionately trusted government agencies (84%) over private companies like Google and Apple (42%;van Souwe et al, 2017), and only accepted surveillance if it was deemed necessary (Kininmonth et al, 2018). Contrasting these established norms, our results imply that Australians are willing to sacrifice privacy to governments and corporations in order to combat the spread of COVID-19.…”
Section: Hypothetical Tracking Scenariosmentioning
confidence: 65%
“…In a recent survey of 100 Australians, Kininmonth et al (2018) found Government surveillance was acceptable when conducted by a "trusted" source for "necessary" reasons, meaning perceptions about the risk from COVID-19 and perception about those collecting the data (e.g., Governments or corporations), will impact public acceptance for COVID-19 tracking technologies.…”
Section: Figurementioning
confidence: 99%
“…The different dimensions of privacy may be experienced to different degrees by the same user and results show that they do not always influence behaviour. The multidimensionality of privacy is an explanation for the sometimes paradoxical disconnect between stated privacy concerns and behaviour (Kininmonth et al 2018;Kokolakis 2017). Our work suggests that though the omnibus scales (Smith, Milberg & Burke 1996) are valuable in eliciting broader perspectives in privacy research, they are not suitable for all research goals.…”
Section: Implications For Theory and Practicementioning
confidence: 89%
“…More recently, Zlatolas et al (2015) tested various dimensions of privacy including values, knowledge and concerns showing different effects of various antecedents. This finding is mirrored by Kininmonth et al (2018), who show that privacy is a multi-dimensional construct and must be studied at a sufficiently granular level to attain meaningful results. Thus, in this research, the collection dimension of privacy is considered, and the following hypothesis is made: H2.…”
Section: Privacy Concernsmentioning
confidence: 90%